AI-Powered Business Intelligence in Manufacturing: A Technical Overview - Indraneel Madabhushini, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Artificial Intelligence (AI) and Business Intelligence (BI) integration in manufacturing environments within the Industry 4.0 framework. The article examines the implementation methodologies, architectural considerations, and performance metrics across various manufacturing domains, including predictive maintenance, quality control, and supply chain optimization. The article demonstrates significant improvements in operational efficiency, cost reduction, and product quality through AI-powered systems. Through detailed analysis of edge computing integration, advanced AI capabilities, and enterprise system architecture, the article provides insights into both current implementations and future technological considerations, offering a roadmap for manufacturing organizations pursuing digital transformation.
Keywords: Artificial Intelligence in Manufacturing; Predictive Maintenance Systems; Smart Manufacturing Analytics; Enterprise System Integration; Edge Computing Implementation